Pengaruh Biological Asset Intensity, Konsentrasi Kepemilikan Dan Profitabilitas Terhadap Pengungkapan Aset Biologis Pada Perusahaan Agrikultur Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2018 - Tika Dian Afifa (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2023)
An agricultural company is a company that is one of unique human activities capable of producing various types of plant and animals.This company also requires disclosure of hielos karmist biological asset, which are the main and important assets in company.Other biological assets intebsit concrenration of ownership, and profitability. The purpose of this research is to examine and analyzethe influenceof biologicalasset intensity, concentration of ownership and profitabilityon disclosure of biological assets.This research is a quantitative reasearchtypr and requires data sources.Secondary data in the form of agricultural company financial report for 2016-2018 data retrieval using descriptive statistical analisys of tears. Based on the research conclusion and the result of the discussion on data analisys shows that biological assets intensity ha no effect on disclosure at blogs.